LDL-cholesterol target achievement in patients with heterozygous familial hypercholesterolemia at Groote Schuur Hospital: Minority at target despite large reductions in LDL-C. (October 2018) - van Delden, Xander M.; Huijgen, Roeland; Wolmarans, Karen H.; Brice, Brigitte C.; Barron, Jennifer K.; Blom, Dirk J.; Marais, A. David
Abstract: Background and aims: Familial hypercholesterolemia (FH) is characterized by markedly increased LDL-cholesterol (LDL-C) and premature cardiovascular disease (CVD). LDL-C lowering is the cornerstone of therapy. The aim of our study was to evaluate LDL-C target achievement and explore reasons for not reaching target in FH patients attending a public-sector lipid clinic at Groote Schuur Hospital in Cape Town, South Africa. Methods: We reviewed clinical records of patients with genetically confirmed heterozygous FH (heFH) retrospectively. For patients seen after 2013, when new guidelines were published, we determined reasons for use of submaximal therapy. Results: Our study population consisted of 776 adult heFH patients. A substantial proportion (41%) of those younger than 50 years of age had already experienced a cardiovascular event. The mean (±SD) untreated and best achieved LDL-C values during follow up were 8.1 ± 2.1 and 4.0 ± 1.5 mmol/l, respectively. Despite a mean LDL-C reduction of 50%, only 140 (25%) achieved an LDL-C ≤ 3.0 mmol/l. Of the 164 participants with follow up after 2013, 42 did not reach LDL-C < 3.0 mmol/l and did not use maximal therapy (26%). The commonest reasons for not using maximum therapy were statin side-effects (n = 15, 36%) and acceptance by the patient (n = 9, 22%) or the physician (n = 8, 19%) of the control achieved. Conclusions: The heFH population in Cape Town is characterized by high baseline LDL-C, a high prevalence of CVD at presentation and low rates of achieving an LDL-C target of 3.0 mmol/l. Highlights: CVD risk is very high in the heFH population from Cape Town that we studied. Despite a mean LDL-C reduction of 50% only 25% achieved a LDL-C < 3, 0 mmol/l. Early identification and aggressive treatment of FH is important. PCSK9 inhibitors should be prescribed based on risk and distance from LDL-C target.